LHPP expression in triple-negative breast cancer promotes tumor growth and metastasis by modulating the tumor microenvironment - Jeffrey Reina; Queralt Vallmajo-Martin; Jia Ning; Aubrey N. Michi; Kay Yeung; Geoffrey M. Wahl; Tony Hunter (Proceedings of the National Academy of Sciences, 2025)
Triple-negative breast cancer (TNBC) is a highly aggressive and metastatic form of breast cancer that lacks an effective targeted therapy. To identify potential therapeutic targets, we investigated the phosphohistidine phosphatase, LHPP, which has been implicated in the development of several types of cancer. However, the full significance of LHPP in cancer progression remains unclear due to our limited understanding of its molecular mechanism. We found that levels of the LHPP phosphohistidine phosphatase were significantly increased in human breast cancer patients compared to normal adjacent tissues, with the highest levels in the TNBC subtype. When LHPP was knocked out in the MDA-MB-231 human TNBC cell line, cell proliferation, wound healing capacity, and invasion were significantly reduced. However, LHPP knockout in TNBC cells did not significantly affect overall phosphohistidine protein levels. Interestingly, LHPP knockout in MDA-MB-231 cells delayed tumor growth and reduced metastasis when orthotopically transplanted into mouse mammary glands. To investigate LHPP’s role in breast cancer progression, we used next-generation sequencing and proximity-labeling proteomics, and found that LHPP regulates gene expression in chemokine-mediated signaling and actin cytoskeleton organization. Depletion of LHPP reduced the presence of tumor-infiltrating macrophages in mouse xenografts. Our results support a tumor promoter role for LHPP phosphohistidine phosphatase in MDA-MB-231TNBC cells and suggest that targeting LHPP phosphatase could be a potential therapeutic strategy for TNBC.